Proposal for the consideration and classification of dimensions, components, and criteria for the self-evaluation of postgraduate programs with a view to the accreditation of a postgraduate program (Innovaciones Educativas, 2024)
This manuscript addresses value assignment in the self-evaluation of postgraduate programs, specifically in the Master's Degree in Integrative Health and Human Movement (MSIMH) of the National University of Costa Rica, based on the national accreditation guidelines. It emphasizes the importance of carrying out this work in a systematic, organized, and clear manner to objectively analyze the aspects that guarantee the quality of the program. Different actors participated in the self-evaluation process, including managers, administrators, teachers, students, and tutors. The results showed that the dimensions "Resources" and "Educational Process" are fundamental, and that special attention should be given to the components "Infrastructure", "Research" and "Academic Staff". Although components such as curriculum and teaching and learning methodology are relevant, it also highlights the importance of academic and financial management for the development and sustainability of the program. It is recommended that future research should contrast the results of the weighting with the results of the MSIMH self-evaluation to identify strengths and areas for improvement in relation to the established weighted values. In short, this study highlights the importance of assigning appropriate values in the self-evaluation of postgraduate programs and encourages the participation of multiple stakeholders in this process. This document can be used as a guide for new processes of value assignment for this type of accreditation.
Keywords: Postgraduate programs; Accreditation; Higher Education; Quality Education; Self-evaluation